Effectiveness of flipped classroom model in distance education: An experimental study in Turkish language course - Aslan, Seda Akti; Turgut, Yigit Emrah; Unlu, Gokhan; Allison, Jordan (Public Library Science, 2025)
This study investigates the impact of the Flipped Classroom Model (FCM) on university students' learning achievement, self-directed learning skills (SLS), and course interaction within the context of live online classes (LOC). Employing a 14-week quasi-experimental design, the research involved an experimental group (n = 34) exposed to the FCM and a control group (n = 25) taught through traditional methods. Pre-tests indicated that the groups were not statistically different at baseline. Post-intervention analyses revealed no statistically significant differences between the groups in terms of immediate learning achievement or course interaction. However, results from a delayed post-test indicated that students in the experimental group demonstrated significantly higher retention of learning content compared to their counterparts. No significant improvements were observed in self-directed learning skills, suggesting that the FCM, as implemented, may not effectively foster such competencies across all learners. Furthermore, the model did not significantly enhance student interaction in the online classroom environment. These findings suggest that while the FCM may support long-term retention, its overall impact on achievement, interaction, and the development of SLS in LOC settings is limited and may be moderated by students' existing self-regulatory capacities.
Keywords: Performance; Improves